Pengaruh pengeluaran pemerintah sektor pendidikan dan kesehatan terhadap indkes pembangunan manusia di kabupaten kutai timur - Kahang, Merang; saleh, Muhammad; Suharto, Rachmad budi (Faculty of Economics and Business Mulawarman University, 2016)
The type of data on research using secondary data is data that has been available to the government agencies involved in this study period of 2009-2014. Model analysis in this study and the multiple linear regression program used to process, classical assumption test data by using SPSS 22. The results of this analysis indicate that government spending education sector (X1) significantly affects the Human Development Index (Y) in East Kutai Regency. Government spending health sector (X2) no significantly affects on the Human Development index (Y) in East Kutai Regency. Showed Government spending health sector (X2) has not been sufficiently realized so well that it is not strong enough boost human development indxs in East Kutai Regency. The results of the research of government spending on education sector (X1) the dominant effect in improving human development indxs in East Kutai Regency.Keyword: Government Sepending Education Sector, Development Secotr Health Expenditure, Human Development Index (HDI).